Just sentencing principles and procedures for a workable system - Frase, Richard S. (Oxford : Oxford University Press, 2013)
This title presents a fully developed punishment theory which incorporates both utilitarian and retributive sentencing purposes. The author describes and defends a hybrid sentencing model that integrates theory and practice - blending and balancing both the competing principles of retribution and rehabilitation and the procedural concern of weighing rules against discretion.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on Nov. 13, 2012).
Keywords: Sentences (Criminal procedure) -- United States -- States; Punishment -- United States -- States; Criminal justice, Administration of -- United States; Sentences (Criminal procedure) -- Philosophy